Valorization of Juglans regia Leaves as Cosmeceutical Ingredients: Bioactivity Evaluation and Final Formulation Development - Nermine Besrour; Taofiq Oludemi; Filipa Mandim; Carla Pereira; Maria Inês Dias; Marina Soković; Dejan Stojković; Olga Ferreira; Isabel C. F. R. Ferreira; Lillian Barros (Antioxidants, 2022)
The cosmetic industry is constantly searching for bioactive ingredients, namely, those obtained from natural sources with environmentally friendly connotations and less toxic effects. A previous study of our research group optimized the extraction of phenolic compounds from Juglans regia by heat-assisted extraction. Due to its richness in different phenolic compounds, the present work aimed to develop a formulation containing J. regia leaf extract. The extract’s antioxidant, anti-tyrosinase, antimicrobial, anti-inflammatory, wound healing, cytotoxicity, and photostability properties were evaluated. The extract was then incorporated into an O/W base cream, followed by characterization of the final formulation in terms of its antioxidant properties, phenolic composition, and stability over time and at different storage conditions. The most abundant compounds in the hydroethanolic extract were 3-O-caffeoylquinic acid (18.30 ± 0.04 mg/g), quercetin-O-pentoside (9.64 ± 0.06 mg/g), and quercetin 3-O-glucoside (6.70 ± 0.19 mg/g). Besides those, the extract presented antioxidant, anti-inflammatory, wound closure, and antibacterial effects against several skin pathogens. In addition, HaCaT cell viability was maintained up to 98% at 400 µg/mL. Within Proteus vulgaris-infected HaCaT cells, the extract also presented an over 40% bacterial mortality rate at its nontoxic concentration (200 µg/mL). After incorporating the extract, the obtained formulation presented a good physicochemical profile over time and at different storage conditions while also maintaining its antioxidant effect; as such, it can be considered stable for topical application. Future work to evaluate its performance in terms of skin permeation and detailed toxicological studies with a focus on regulatory requirements, involving skin irritation, eye irritation, genotoxicity, photo-irritation, and dermal absorption, should be conducted, as the prepared formulation demonstrated relevant properties that deserve to be further explored.